The “golden key”: A novel approach to teaching/learning Biology in a secondary school in Brazil: A cultural historical activity theory approach. - Hardman, J.; Borget Corte, V. (South African Journal of Higher Education, 2023)
The importance of developing students’ conceptual understanding of biological science in school is well established as a precursor to future development (Cachapuz et al. 2005). However, students continue to underperform in this important scholastic area due in large part to not engaging in the deeper concepts taught. In this article we investigate an interdisciplinary approach to teaching biology in a school in Brazil. We draw on the theoretical concepts provided by Cultural Historical Activity Theory (CHAT) to unpack how interdisciplinary teaching, across different activity systems, can lead to shifts in the activity systems, with students developing a deeper conceptual understanding of biology. Seven teachers (from chemistry, biology, the arts, and geography) and 196 students form the participants in this study. Findings indicate that contradictions arising both within and between activity systems across the teaching contexts led to students’ object shifting from merely covering the curriculum to developing a deeper understanding of biological concepts.